Exchange rate policy and the relative distribution of FDI among host countries - Yuqing Xing (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
This paper examines the FDI-exchange rate nexus in the context of one FDI source and two host countries.It focuses on the effect of exchange rates on relative FDI inflows between the two host countries.The theoretical analysis shows explicitly that relative FDI inflows are a function of relative real exchange rates.In particular, if one host country devalues its currency against that of the source country more than the other does, FDI into the former country will be expected to increase relative to the other country. The theoretical inference is examined with Japanese FDI in manufacturing industries of China and ASEAN-4 (Indonesia, Malaysia, the Philippines and Thailand).The empirical results generally support the theoretical conclusion, suggesting that the real devaluation of the Chinese Yuan undercut FDI into the ASEAN-4.
URN:NBN:fi:bof-201408072034
Keywords: F14; F23; F31; 330; FDI; Exchange rate; China; ASEAN-4